Syrian Partisan Press Coverage of The Presidential Elections2021 Analytical study of Al-Baath Newspaper (Damascus University Journal of arts and humanities sciences, 2024)
The study aimed to find out the extent of interest of the Syrian partisan press in the news coverage of the presidential elections for the year 2021 AD, and to identify the most important electoral contents that gained its attention, and to monitor the type of coverage approved, and to reveal its sources; In addition to knowing the journalistic arts used, and the typographical elements (photos - website - titles) used in covering Syrian electoral topics.This study falls within the descriptive research, and adopts the media survey method; Using the content analysis tool, the researcher followed the comprehensive survey method in extracting the study sample items from Al-Baath newspaper; This was during the study period from 1/5/2021AD to 1/6/2021, so the sample drawn amounted to 24 numbers. The study reached a number of results, most notably: the events and festivals supporting the presidential elections attracted the attention of the Syrian partisan newspapers, the sample of the study, due to their desire to highlight the Syrians’ desire and readiness to hold elections; Followed by the regulatory and oversight process to complete the electoral process. News tops the list of goals that the newspaper seeks to achieve by publishing the contents relatedto the Syrian presidential elections in 2021 AD, followed by the goal of political mobilization in the second place, while the goal of monitoring the interests of society came in third place, and the trend prevailed Positive (pro-election) on the electoral contents covered by the Baath newspaper; Being a pro-newspaper issued by the ruling party of the state and society.
Keywords: press coverage; Syrian partisan press; presidential elections; content analysis